Association between vitamin D levels and mortality in hemodialysis patients: a cohort study - da Silva Canhos, Maryanne Machado [UNESP] (2020)
Introduction: Low vitamin D levels are associated with mortality in hemodialysis (HD) patients; however, the serum vitamin D thresholds are unclear. This study aimed to identify the vitamin D level below which mortality increases in HD patients. Methods: A cohort of HD patients enrolled from January 2014 to January 2017 was evaluated. The variables were analyzed according to the season, namely, summer, winter, and annual average, mortality was the primary outcome. The patients were assigned to vitamin D quintiles, and multivariate Cox regression analysis adjusted for age, ethnicity, gender, body mass index (BMI), inhibitors of the renin-angiotensin system, statin, calcitriol, and antiplatelet drugs use, hemodialysis vintage, hypertension, diabetes mellitus, atherosclerotic disease, and C-reactive protein was performed. Results: There were studied 306 patients. Vitamin D levels of 18.0–23.6 ng/mL (hazard ratio [HR] = 4.30; 95% confidence interval [CI] 1.60–11.54, p = 0.004) and <18.0 ng/mL (HR = 3.83; 95% CI: 1.42–10.35, p = 0.008) in summer and vitamin D levels of 21.5-27.1 ng/mL (HR = 3.70; 95% CI: 1.50-9.11, p = 0.004) and ≤17.5 ng/mL (HR = 2.84; 95% CI: 1.13–7.13, p = 0.026) in winter were associated with mortality. The average annual values of vitamin D associated with all-cause mortality were <17.7 ng/dL (adjusted HR = 4.25, 95% CI: 1.57–11.48, p = 0.004), and between >17.7 ng/dL and ≤23.1 ng/dL (adjusted HR = 3.91, 95% CI: 1.47–10.42, p = 0.006). Conclusions: Annual average vitamin D levels <23.1 ng/mL were associated with higher all-cause mortality, regardless of the confounding variables evaluated.